2022
DOI: 10.3390/biom12111662
|View full text |Cite
|
Sign up to set email alerts
|

The HLA-DRB1*07 Allele Is Associated with Interstitial Lung Abnormalities (ILA) and Subpleural Location in a Mexican Mestizo Population

Abstract: Interstitial lung abnormalities (ILA) are defined as the presence of different patterns of increased lung density, including ground glass attenuation and reticular opacities on chest high-resolution computed tomography (HRCT). In this study, we included 90 subjects with ILA and 189 healthy controls (HC) from our Aging Lung Program. We found that subjects with ILA are older, have a significant smoking history, and have worse pulmonary function than HC (p < 0.05). When we evaluated the allele frequencies of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Risk factors for the presence of ILA, other than cigarette smoking, include increasing age, other inhalational exposures (e.g., vapors, gases, dust, fumes, traffic-related air pollution such as nitrogen oxides or carbon), some biomarkers and genetic factors [ 6 , 10 , 11 , 12 , 13 , 14 ]. Regarding genetic factors, a piece of evidence has been found that associates HLA-DRB1*14 allele with increased risk for developing ILA, especially those of subpleural location [ 15 ]. The systematic evaluation of large cohorts has shown a prevalence of ILA in 2–9% of cigarette smokers and 2–7% of non-smokers [ 7 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Risk factors for the presence of ILA, other than cigarette smoking, include increasing age, other inhalational exposures (e.g., vapors, gases, dust, fumes, traffic-related air pollution such as nitrogen oxides or carbon), some biomarkers and genetic factors [ 6 , 10 , 11 , 12 , 13 , 14 ]. Regarding genetic factors, a piece of evidence has been found that associates HLA-DRB1*14 allele with increased risk for developing ILA, especially those of subpleural location [ 15 ]. The systematic evaluation of large cohorts has shown a prevalence of ILA in 2–9% of cigarette smokers and 2–7% of non-smokers [ 7 , 16 ].…”
Section: Introductionmentioning
confidence: 99%